Hubungan antara Pengetahuan Tentang Merokok dan Motivasi Merokok dengan Jumlah Rokok yang Dikonsumsi - Aisya Fikritama Aditya; . Harsini; . Muthmainah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Tobacco has high level of consumption in Indonesia and also has impact to the health and social-economic factors. Nearly all smokers in Indonesia considered hat smoking is a necessity. Smoking habits are influenced by some factors, some of them are theknowledge of smoking and smoking motivation. This study aims to determine the correlation between knowledge of smoking and smoking motivation with the number of cigarettes consumed. Methods: This study was an observational study with cross sectional analysis. A total of 75 subjects were selected by simple random sampling. Samples were first grade students of Veteran University Sukoharjo who smoke. Data was collected by distributing questionnaires consist of knowledge of smoking and smoking motivation to respondents. Data was analyzed by using multiple linear regressionmodel. Results: This study showed the value of the Pearson correlation r = -0.574, p = 0.000, which means there was a negative correlation that statistically significant between the knowledge of smoking and number of cigarettes consumed, and r = 0.872, p = 0.000, which means there was a positive correlation that statistically significant between smoking motivation and number of cigarettes consumed. Multiple linear regression test showed the results of Adjusted R-square value 0.783 which means the influence of knowledge of smoking and smoking motivation to the number of cigarettes consumedwere 78.3 %, while the remaining 21.7 % came from other factors. Conclusions: There was a significant correlation between knowledge of smoking and smoking motivation with the number of cigarettes consumed. Keywords: knowledge, motivation, smoking, number of cigarettes